2022
DOI: 10.1007/s11920-022-01390-9
|View full text |Cite
|
Sign up to set email alerts
|

Executive Functioning Constructs in Anxiety, Obsessive–Compulsive, Post-Traumatic Stress, and Related Disorders

Abstract: Purpose of Review We synthesize theories proposing complex relations between cognitive functioning and anxiety-related concepts. We evaluate vulnerability theories suggesting that deficits in various cognitive functioning domains predict future anxiety-associated concepts. We examine scar theories asserting the opposite direction of effects (i.e., anxiety predicting cognitive dysfunction). Furthermore, we examine more novel frameworks on this topic. Recent Findings Reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…The results revealed that the level of cognitive control, rumination, and worry was not significantly different in both groups of MDD and GAD. Defects in the cognitive control of this group of patients can indicate common mechanisms in the development and continuation of emotional disorders (Zainal & Newman, 2022). This dysfunction in cognitive control can make a person more vulnerable to repetitive thoughts of rumination and worry (Bartholomay et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that the level of cognitive control, rumination, and worry was not significantly different in both groups of MDD and GAD. Defects in the cognitive control of this group of patients can indicate common mechanisms in the development and continuation of emotional disorders (Zainal & Newman, 2022). This dysfunction in cognitive control can make a person more vulnerable to repetitive thoughts of rumination and worry (Bartholomay et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…These patterns consistently manifested in daily life across different situations, with worry initiating and maintaining anxiety while predicting a decreased likelihood of significant increases in negative emotions in future periods [22, 23, 83, 84]. Cognitively, GAD has been associated with increased focus on threats [85], the tendency to interpret ambiguous material negatively [86], and executive dysfunction [87]. In summary, targeting reduction in reactivity to inner experience could enhance the effectiveness of brief MEMIs for GAD by honing specific skills to mitigate emotional or stress reactivity across multiple biopsychosocial dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…First, all putative mediators and clinical outcome measures relied on web-based self-reports. Future RCTs should incorporate diverse measures of related constructs and evaluate crucial yet understudied factors believed to drive change, such as attentional bias toward threats [114,115], executive functioning [102,116,117], and physiological anxiety indices [118,119]. Second, we did not evaluate the sustainability of mindfulness skill use after the 2-week intervention duration.…”
Section: Limitations and Strengthsmentioning
confidence: 99%